INVESTIGATING STUDENTS’ ABILITY TO USE GERUND AND PRESENT PARTICIPLE AT ENGLISH EDUCATION DEPARTMENT OF SORONG MUHAMMADIYAH UNIVERSITY - Muhaiminah Akib; Hayat Marwan Ohorella (Qalam : Jurnal Ilmu Kependidikan, 2018)
This research presented analysing the students’ ability to use gerund and present participle at English Education Department of Sorong Muhammadiyah University and the factors affecting the students’ ability to use gerund and present participle. This research used descriptive method with the test and questionnaire instruments. The test consisted of 30 items and the questionnaire consisted of 23 items. The population of the research was the students of English Education Department of Sorong Muhammadiyah University in academic year 2011/2012 that consistent of 423 students. The sample of this research consisted of 43 students taken by applying purposive sampling technique.  The result of the data analysis indicated that the students’ ability to use gerund and present participle was poor. It was indicated by the rate of percentage of the students’ score obtained through in which out of 43 students, 3 students (7 %) got very poor score, 19 students (44.2%) got poor score, 20 students (46.5%) got fairly score, and 1 (2.3%) students got good score. While none of them got very good score. The mean score of the test was 5.41 that falls into poor classification. The finding showed that the factors affected the students’ ability to use gerund and present participle because the same form of gerund and present participle, the students did not know about the use of gerund and present participle and the students lack ability of memorizing.